2016
DOI: 10.13060/00380288.2016.52.4.270
|View full text |Cite
|
Sign up to set email alerts
|

Transitions between Employment and Unemployment among Older Workers in the Czech Republic

Abstract: There is a sharp discrepancy between the emphasis being placed on active ageing and labour market participation in older age and the high unemployment rates observed among older workers. Cross-sectional data in the Czech Republic consistently present evidence of job insecurity and employment vulnerability in older age groups. Aggregated data and statistical indices do not, however, offer a suffi ciently detailed picture of the social processes (e.g. exit from the labour market, duration of unemployment, and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…The unemployment rate and the possibility of getting a job have a significant impact on the activity of this category. In principle, it can be concluded that the economic activity of the 55+ generation is influenced by objective factors, in particular the state policy in the field of obtaining retirement rights and employment opportunities (Walker and Maltby, 2012;Boudiny, 2013;Foster and Walker, 2015;Zelezna and Kreidl, 2016) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The unemployment rate and the possibility of getting a job have a significant impact on the activity of this category. In principle, it can be concluded that the economic activity of the 55+ generation is influenced by objective factors, in particular the state policy in the field of obtaining retirement rights and employment opportunities (Walker and Maltby, 2012;Boudiny, 2013;Foster and Walker, 2015;Zelezna and Kreidl, 2016) .…”
Section: Discussionmentioning
confidence: 99%
“…Professional activation influences the use of older workers' potential, their knowledge and skills. Knowledge of older employees can be passed on to the younger generation in specific areas of work, enrich their social capital, accumulate experience in the functioning of the firm (Zelezna & Kreidl, 2016;Kartuzova, 2020;Roman-Gravan et al, 2021).…”
Section: Literature Review: Attitude Professional Work Concept Of Pop...mentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting the growth of the employment of older people is a preferred trend in countries where the use of employment potential of older people in the labor market is closely linked to the demographic phenomenon of population aging (Jeníček & Foltýn, 2003;Dudel & Myrskylä, 2017;Ćwirlej-Sozańska et al, 2018;Neary et al, 2019;Horváthová & Éhn, 2020;Vaňo, 2020), the problem of the growing economic dependence of older people (Hu & Yang, 2012;Fiala & Langhamrova, 2017;Abeysinghe, 2019;Hyndman et al, 2021) and unemployment among older people (Axelrad et al, 2017;Amber & Domingo, 2017;Axelrad et al, 2018;Zelezna & Kreidl, 2016), especially those just before retirement age (Gomezbellenge & Belgrave, 1984;Wuebbeke, 2011;Murray et al, 2015;Hetschko et al, 2019;Ponomarenko et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Také v empirických výzkumech se objevují analýzy, které vzájemně utvářený vliv (znevýhodňujících) faktorů analyzují [např. Železná, Kreidl 2016]. Intersekcionální přístup navazuje na zkoumání kategorií hierarchizujících a kategorií utvářejících mocenské vztahy s důrazem na propojenost a situovanost znevýhodňujících kategorií v sociálním, ekonomickém a politickém kontextu [Collins 1990: 276].…”
Section: Intersekcionální Perspektivaunclassified